Qarakhanid Roads to China A History of Sino-Turkic Relations - Duturaeva, Dilnoza (Handbook of Oriental Studies. Section 8 Uralic & Central Asian Studies, 2022)
Qarakhanid Roads to China takes readers on a large-scale adventure with envoys and merchants, monks and artists, men and women along the Silk Roads and beyond.